2005
DOI: 10.1007/s11176-005-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Laser Desorption Ionization of Arylene Phenylphosphonites Formed by Condensation of Dihydric Phenols with Phenylphosphonous Bis(diethylamide)

Abstract: Step high-temperature condensation of dihydric phenols [1,4-dihydroxybenzene, 4,4`-dihydroxybiphenyl, and 2,2'-bis(4-hydroxyphenyl)propane] with phenylphosphonous bis(diethylamide) is carried out. The molecular weight, composition, and structure of the resulting oligomeric arylene phenylphosphonites were assessed by means of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The widest mass range was observed in the mass spectrum of 4,4`-dihydroxybiphenyl, which corresponds to an oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…In spite of the potential difficulties described above, the trueM¯ns determined by SEC are in good agreement with those calculated from the 31 P{ 1 H} NMR integrations, with all values being greater than 10 4 Da (Table ). These molecular weights are of the same order of magnitude as reported for poly(H‐phosphonates) and are an order of magnitude greater than those reported for the similar poly(arylene phenylphosphonates) . The good agreement between trueM¯ns determined by the two methods suggests that the polyphosphonates are primarily linear chains with essentially no cyclic oligomers present.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In spite of the potential difficulties described above, the trueM¯ns determined by SEC are in good agreement with those calculated from the 31 P{ 1 H} NMR integrations, with all values being greater than 10 4 Da (Table ). These molecular weights are of the same order of magnitude as reported for poly(H‐phosphonates) and are an order of magnitude greater than those reported for the similar poly(arylene phenylphosphonates) . The good agreement between trueM¯ns determined by the two methods suggests that the polyphosphonates are primarily linear chains with essentially no cyclic oligomers present.…”
Section: Resultssupporting
confidence: 65%
“…However, Nifant'ev et al . have reported that attempts to synthesize poly(phenylphosphonites) (Chart ; R = Ph, R′ = arylene, X = ··) using either this method or a slightly modified sonochemical method gave relatively low molecular weights of 6 − 9 kDa presumably due to side reactions that terminated the polymerization …”
Section: Introductionmentioning
confidence: 99%
“…This behavior suggested that BDM was heat sensitive. This result is similar to those of Nifant'ev et al in which thermal decomposition of a polyphosphonite derived from bisphenol‐A, which has a higher melting point than does 1,4‐benzenediemethanol, 19,20 was observed. To avoid thermal decomposition of the BDM polymers, the reactions conditions were altered to minimize exposure to high temperatures.…”
Section: Resultssupporting
confidence: 90%
“…We previously reported that polyphosphonates with moderately high molecular weights could be prepared by the polycondensations of 1,12‐dodecanediol with bis(diethylamino)arylphosphines (aryl=phenyl, 2,2′‐bithiophenyl) followed by oxidation with a chalcogen 21 . While this result was extremely promising for the synthesis of these highly modular polymers, some literature suggested that the polycondensation might not work with all diols 19,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation